2022
DOI: 10.1007/s13201-022-01609-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality for drinking and irrigation in the Timahdite–Almis Guigou area (Middle Atlas, Morocco)

Abstract: The groundwater in the Timahdite–Almis Guigou area flows through fluvio-lacustrine and volcanic formations of Plio-Quaternary age and Liassic limestone. The groundwater resources in this area are used for drinking water and irrigation of agricultural plots. 18 groundwater samples were collected for this study. The physico-chemical and bacteriological parameters analysed, such as temperature, electrical conductivity, pH, dissolved oxygen, Na+, K+, Ca2+, Mg2+, Cl−, HCO3−, SO42−, NO2−, NO3−, faecal Coliforms, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…10). This diagram (Richards, 1954), sometimes referred to as Riverside diagram (Alsubih et al 2022;Amrani, 2022), is very helpful to enhance the analysis of SAR and EC parameters. It should be noted that the SAR classes are equivilant to those used above, but the EC classes are slightly different.…”
Section: Water Qualitymentioning
confidence: 99%
“…10). This diagram (Richards, 1954), sometimes referred to as Riverside diagram (Alsubih et al 2022;Amrani, 2022), is very helpful to enhance the analysis of SAR and EC parameters. It should be noted that the SAR classes are equivilant to those used above, but the EC classes are slightly different.…”
Section: Water Qualitymentioning
confidence: 99%
“…1). It covers an area of 20,000 km 2 , with a population reaching 297,000 in 2018. The geographical coordinates of the study area are 05°00'00"/5°45'00"E and 31°47'33'/32°30'00"N. Agriculture is the main activity in the region of Ouargla.…”
Section: Study Area Location Geomorphology and Climatementioning
confidence: 99%
“…Journal of Ecological Engineering 2023, 24 (2), 279-294 (56.3%) and Ca-Cl (43.7%) facies. In addition, analysis of bivariate plots between chemical parameters and calculation of saturation indices of major minerals showed that mineralization of CI waters is controlled by rock-water interactions, including silicate alteration, evaporite dissolution and cation exchange.…”
mentioning
confidence: 99%
“…They determined that spatial distribution maps of the studied area offer dependable information for policymakers in a highly sustainable manner. Amrani et al, (2022) evaluated the suitability of groundwater for drinking and irrigation in the Timahdite-Almis Guigou region of Morocco. Their findings suggested fluctuating qualities of groundwater, ranging from good to poor for drinking purposes while signifying that the groundwater was suitable for irrigation.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%